Pengaruh Hubungan Sosial Antar Siswa terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Siswa Kelas VII di SMPN 1 Kec Payakumbuh - Istiqomah Istiqomah; Salmi Wati; Wedra Aprison; Charles Charles (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Finding out how students' social ties impacted their performance in Islamic Religious Education classes at SMPN 1 Kec Payakumbuh was the driving force for this research. Quantitative correlational study is the method employed. A total of 256 seventh graders made up the study's population, and 64 students were selected using a proportionate stratified random sampling technique. Questionnaires and other data analysis methods such as descriptive statistics, hypothesis testing, and data analysis precondition tests were utilized for data collecting. The study's findings show that students' social ties have a significant impact on learning outcomes, with a significance value of 0.009 <0.05. Therefore, we can accept Ha and reject H0.